Tabrizicola rongguiensis sp. nov., isolated from the sediment of a river in Ronggui, Foshan city, China. Issue 10 (19th October 2022) - Xu, Jiarou; Deng, Tongchu; Huang, Youda; Dong, Meijun; Yang, Shan; Xu, Meiying
Abstract : A novel Gram-negative, aerobic, non-spore-forming, non-motile and rod-shaped bacterium, designated J26 T, was isolated from the sediment of a river in Ronggui, Foshan city, China. Strain J26 T grew optimally at 0 % (w/v) NaCl, pH 6.5–7.5, and 30 °C, and it formed milky white irregular colonies on Reasoner's 2A agar medium. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain J26 T had the highest similarity to Tabrizicola aquatica RCRI19 T (97.1 %) and formed a distinct clade in the genus Tabrizicola . Cellular components of J26 T supported this strain as a member of the genus Tabrizicola . The predominant fatty acids were C18 : 1 ω 7 c, C18 : 1 ω 7 c -11 methyl and C16 : 0 . Polar lipids were diphosphatidylglycerol, phosphatidylglycerol and phosphorylethanolamine. Ubiquinone Q-10 was the major respiratory quinone, and the DNA G+C content was 64.2 mol%. However, low 16S rRNA gene sequence similarity and average nucleotide identity (73.56 % for ANIb between strain J26 T with RCRI19 T ) demonstrated that strain J26 T should be assigned to a novel species. Moreover, the differences between J26 T and RCRI19 T in terms of physiological and biochemical properties, such as carbon, nitrogen and sulphur metabolism, further supported that J26 T represents a novel species, for which the name Tabrizicola rongguiensis sp. nov. is proposed. The type strain is J26 T (=GDMCC 1.2843 T =KCTC 92112 T ).